Warehouse performance improvement during big event using discrete event simulation approach : A case study of food and beverages company in Shah Alam - Muhammad Amar Azamuddin, Abd Ghafar; Fazeeda, Mohamad (Universiti Malaysia Pahang, 2023)
The purpose of this study is to see how customer demand changes when Malaysian e-commerce hosts a major event affect the warehouse operations. This is due to the fact that, when compared to non-major events, the pricing are very reasonable. As a result, when the major events happen, e-commerce especially the warehouse operations will face significant challenges in managing customer orders. Long lines can be found in the picking and packing sections. Orders will then be shipped later than anticipated. In this study, Company X is one of the e-commerce companies affected by this issue. Discrete Event Simulation (DES) was used as the method in measuring the warehouse performance under study. By introducing several scenarios that are appropriate for company X, the company's warehouse performance is found to be more efficient in terms of reducing process queuing time and resource utilization.